(3GdEMUGA GdESJOdGdjs - (3MSf jGSjf(B, (3WYeIs; (3EjeGf MSjf MfhT(B, s ((3YeGf(B:s (3OGQ UaGA ddfTQ hGdJhRjY(B,s, 2010)
(3fXQjI GdeLehYGJ hWQb GdYO(B- (3eONd Gdi fXQjI GdEMJeGd(B- (3GdeJZjQGJ GdYThGFjI hJhRjYGJgG GdEMJeGdjI(B- (3CSdhH GdYjfGJ hWQb ENJjGQgG(B- (3GdeYGjfI GdEMUGFjI hJhRjYGJgG(B- (3fXQjI GdJbOjQ(B- (3ENJHGQ GdaQVjGJ GdEMUGFjI(B- (3GdENJHGQGJ GdeSJfOI Ydi GdJhRjY GdWHjYj(B- (3GdENJHGQGJ GdeSJfOI Ydi JhRjY(B- (3GdENJHGQGJ GdeSJfOI Ydi JhRjY eQHY cGj(B- (3GdENJHGQGJ GdeSJfOI Ydi JhRjYs
Keywords: (3GdEMUGA GdESJOdGdjs; (3GdEMUGA GdhUajs; (3GdESJOdGd GdEMUGFjs